EFEK HARGA, PROMOSI DAN KUALITAS PELAYANAN TERHADAP KESETIAAN PELANGGAN, MELALUI KEPUASAN KONSUMEN PADA KING BURGER DI KOTA BATAM - Raja Silvia Rica Lucinda; Jazuli Jazuli (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
During the current period the state of competition is increasingly proliferated and become more intense in the fast food business developments. Each company should be able to create a viable strategy in following the competition. The strategy is not only done on price or promotion, but the quality of service that can satisfy the customer when the service was done. Data were collected by distributing questionnaires to 93 respondents question the method of distributing the questionnaire. This study shows that the results of the structural model I, direct sale and service quality has a significant relationship with customer satisfaction. Structural II directly on price, promotion and customer satisfaction significantly influence customer loyalty and indirectly through Customer Satisfaction Service Quality significant effect on customer loyalty. The value of R Square = 0.768 indicates that Price, Promotion, Quality of Service and Customer Satisfaction to Customer Loyalty of 76.8% while the remaining 23.2% was contributed by other factors outside of the study. The conclusion from this research, either directly or indirectly through customer satisfaction service quality variables more significant effect on customer loyalty of the variable Price and Promotion. The implication of this research is need for increased promotion and price policyKeywords: Pricing, Promotion, Service Quality, Satisfaction, Loyalty, Customer.